Effect of Traditional Stir-Frying on the Characteristics and Quality of Mutton Sao Zi - Bai, Shuang; You, Liqin; Wang, Yongrui; Luo, Ruiming (Frontiers in Nutrition, 2022)
The effects of stir-frying stage and time on the formation of Maillard reaction products (MRP) and potentially hazardous substances with time in stir-fried mutton sao zi were investigated. Furosine, fluorescence intensity, Nε-(1-carboxymethyl)-L-lysine (CML), Nε-(1-carboxyethyl)-L-lysine (CEL) polyaromatic hydrocarbons (PAHs), heterocyclic aromatic amines (HAAs) and acrylamides (AA) mainly presented of stir-fried mutton sao zi. The furosine decreased after mixed stir-frying (MSF) 160 s due to its degradation as the Maillard reaction (MR) progressed. The fluorescent compound gradually increased with time during the stir-frying process. The CML and CEL peaked in MSF 200 s. AA reached its maximum in MSF 120s and then decreased. All the 5 HAAs were detected after MSF 200 s, suggesting that the stir-frying mutton sao zi was at its best before MSF 200 s. When the stir-frying exceeded the optimal processing time of (MSF 160 s) 200 s, the benzo[a]pyrene peaked 0.82 μg/kg, far lower than the maximum permissible value specified by the Commission of the European Communities. The extended stir-frying promoted MRP and some hazardous substances, but the content of potentially hazardous substances was still within the safety range for food.